Social Support and COVID-19 Stress Among Immigrants in South Korea - Souhyun Jang; Paul Youngbin Kim; Min-Sun Kim; Hoyoun Koh; Kyungmin Baek (Asian Journal for Public Opinion Research)
Individuals have been under more stress since the COVID-19 pandemic began than they were before the pandemic. While social support is a known stress buffer among the general population, its impact on stress among vulnerable populations, such as immigrants and those living in rural areas, has received little attention in the context of South Korea. Accordingly, we examined the relationship between different types of social support and COVID-19 stress among young adult immigrants based on where they live (rural vs. urban). We conducted a survey of 300 young adult immigrants aged 25--34 years and analyzed the results. The dependent variable was COVID-19 stress, and the independent variables were four types of social support: emotional, appraisal, instrumental, and informational. We discovered that young adult immigrants in rural areas perceived higher-level social support in all aspects compared with those in urban areas. Furthermore, social support was not related to COVID-19 stress in urban areas, while appraisal support was positively and informational support was negatively related to COVID-19 stress in rural areas. Our findings suggest that a contextualized understanding of social support is critical to understanding COVID-related stress during the COVID-19 pandemic.